2015
DOI: 10.1108/ijqrm-12-2013-0193
|View full text |Cite
|
Sign up to set email alerts
|

Total quality management (TQM) movement in public health

Abstract: Purpose – The purpose of this paper is to suggest better methods for monitoring the diagnostic and treatment services for providers of public health and the management of public health services. In particular, the authors examine the construction and use of industrial quality control methods as applied to the public providers, in both the prevention and cure for infectious diseases and the quality of public health care providers in such applications including water quality standards, sewage man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 49 publications
0
3
0
3
Order By: Relevance
“…Considering the size, SMEs have more simple process compared to large enterprises (Aamer et al , 2017; Maistry et al , 2017; Teixeira et al , 2015). Informal quality assurance system of SMEs have made regular monitoring system and benchmarking of current process much difficult (Aamer et al , 2017; Jarrett, 2016). However, knowledge about the cost of poor quality is very little in SMEs compared to large industries (Van Schoten et al , 2016; Teixeira et al , 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Considering the size, SMEs have more simple process compared to large enterprises (Aamer et al , 2017; Maistry et al , 2017; Teixeira et al , 2015). Informal quality assurance system of SMEs have made regular monitoring system and benchmarking of current process much difficult (Aamer et al , 2017; Jarrett, 2016). However, knowledge about the cost of poor quality is very little in SMEs compared to large industries (Van Schoten et al , 2016; Teixeira et al , 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For other researchers (Aladwan and Forrester, 2016;Giaccio, 2013;Vanichchinchai and Igel, 2011;Weckenmann et al, 2015), TQM is a management philosophy that encompasses the entire organization activities to reach operational excellence. The interesting substance of TQM is the concept of total quality in achieving the goals of organization, such as top management commitment, gradual principle in achieving quality, continuous improvement, commitment refraction of top management in the cultivation of culture, and work ethic in all organizational lines ( Jarrett, 2016). Empirical studies reported various benefits of TQM implementation including among others improvement in productivity and efficiency, improved employee morale, better market shares, quality improvement, cost savings, improved financial performance, an increase in employee performance, and competitive advantages (Mosadeghrad, 2015;Sadikoglu and Zehir, 2010;Weckenmann et al, 2015;Zairi, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…TQM контролирует все процессы преобразования организации, чтобы лучше удовлетворять потребности клиентов наиболее экономичным способом (Andersen HV, et al, 2004). Три принципа, которые характеризуют TQM, -это ориентация на клиента, постоянное совершенствование и тимбилдинг (работа в команде) [18][19][20][21].…”
Section: подходы к управлению качествомunclassified